2021
DOI: 10.3390/jrfm14010027
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Capital and Bank Risk in Vietnam—A Quantile Regression Approach

Abstract: This study empirically presents evidence of nonlinearity and heterogeneity relation between intellectual capital and risk-taking for the Vietnamese banking system. We used quantile regression methods on a data set of 30 Vietnamese banks from 2007 to 2019. The results showed that bank insolvency was positively affected by its value-added intellectual coefficient (VAIC) at the upper quantiles (i.e., 80th and 90th), while the opposite was true for credit risk (i.e., 10th and 20th quantiles). When observing the VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…The empirical results from both models show that firm performance in Vietnam is significantly affected by the capital employed efficiency. This finding is consistent with previous studies (Nguyen et al, 2021; Zhang et al, 2021). However, Vietnamese firms have yet to tap into the full potential of structural capital efficiency through processes, patents, and goodwill (Vo & Tran, 2021).…”
Section: Empirical Results and Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The empirical results from both models show that firm performance in Vietnam is significantly affected by the capital employed efficiency. This finding is consistent with previous studies (Nguyen et al, 2021; Zhang et al, 2021). However, Vietnamese firms have yet to tap into the full potential of structural capital efficiency through processes, patents, and goodwill (Vo & Tran, 2021).…”
Section: Empirical Results and Discussionsupporting
confidence: 94%
“…They conclude that intellectual capital significantly and positively contributes to the bank's performance in Vietnam. Nguyen et al (2021) examine the relationship between intellectual capital and risk-taking in the Vietnamese banking system from 2007 to 2019. They reveal that intellectual capital has an inversed U-shaped relationship with bank risk-taking.…”
Section: Corporate Governance Intellectual Capital and Firm's Perform...mentioning
confidence: 99%
See 1 more Smart Citation
“…Tran et al (2020) confirm a significant relationship between CG and intellectual capital in Vietnam. Nguyen et al (2021) assert that intellectual capital plays a crucial role in a firm’s performance in Vietnam. However, limited evidence has been found to contribute to the understanding of linkages between intellectual capital, CG and CSR (Buallay and Hamdan, 2019; Altuner et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For relevant studies in the Vietnamese banking industry, the recent empirical results found by Le and Nguyen ( 2020 ) and Nguyen et al ( 2021 ) show that it is arguable whether IC has provided advantages for banks or not. Specifically, by employing the system GMM method, the findings of these authors prove that although VAIC and its components positively affect the profitability of banks and the role of VAIC, and HCE tends to be clearly evident in state-owned and foreign banks, these relationships may be inverse U-shaped, particularly in the cases of VAIC, CEE and HCE.…”
Section: Literature Reviewmentioning
confidence: 99%